Standar Kompetensi Kelulusan - Maharani, Kiki (Borneo Journal of Islamic Education, 2022)
Abstract Their level of intelligence determines the quality of human resources. Intelligence is not limited to a single feature, but encompasses multiple domains. Obviously, this is acquired through education by every individual. The quality of education determines the development of a nation. According to government regulation number 32 of 2013, the Indonesian government establishes eight national education standards that apply to all levels of education. The Graduate Competency Standards are one of the eight standards and one of the factors that determine the quality of education in Indonesia. It is desired that each individual may contribute to the nation's growth by creating the most qualified graduates and adhering to current norms. However, fraud is still discovered during its deployment, diminishing the quality of graduate students. The physical position of Indonesia has also become a major concern, as it has become a benchmark for all regions in the country. The government remains committed to minimizing all challenges based on their nature. As a remedy to the problem of graduate competency standards, numerous programs and policies were developed. It requires cooperation from a variety of parties so that every educational problem, particularly those in the field of education, may be resolved effectively and Indonesia's education system can continue to improve. Keywords: Graduate Competency Standards, National Education Standards, Indonesian Education Abstrak Kualitas sumber daya manusia ditentukan berdasarkan tingkat keceerdasannya. Kecerdasan tidak hanya di satu aspek namun di berbagai bidang. Hal ini tentunya diperoleh setiap individu melalui bangku pendidikan. Kemajuan suatu bangsa ditentukan oleh kualitas pendidikannya. Pemerintah Indonesia menetapkan 8 standar nasional pendidikan yang di aplikasikan pasa setiap jenjang pendidikan sebagaimana di atur dalam peraturan pemerintah no 32 tahun 2013. Salah satu dari 8 standar tersebut adalah Standar Kompetensi Lulusan yang menjadi salah satu penentu kualitas pendidikan di Indonesia. Dengan menghasilkan lulusan terbaik atau telah memenuhi standar yang ada diharapkan setiap individu tersebut dapat berkontribusi dalam perkembangan bangsa. Namun dalam pelaksanannya masih saja ditemukan kecurangan yang menurunkan kualitas lulusan peserta didik. Letak geografis Indonesia pun menjadi salah satu isu yang cukup menjadi perhatian karena merujuk pada standar yang berarti menjadi patokan bagi selurtuh wilayah di Indonesia. Pemerintah terus mengupayakan untuk meminimalisir segala permasalahan sesuai dengan jenisnya. Berbagai program dan kebijakan dikeluarkan sebagai solusi permasalahan standar kompetensi lulusan ini. Perlu dukungan dari berbagai pihak agar setiap permasalahan pendidikan khususnya permasalahan dalam bidang pendidikan dapat teratasi dengan baik sehingga perkembangan pendidikan di Indonesia menjadi lebih baik lagi. Keywords: Standar Kompetensi Kelulusan, Standar Nasional Pendidikan, Pendidikan Indonesia